Short-term functional outcomes of a delayed single-stage reconstruction of chronic posterior cruciate ligament and posterolateral corner deficiency - Abdullah, Mohd. Rusdi; Ahmad, Shahrulazua; Tahir, Siti Hawa; Mohd Nasir , Mohd Nizlan (Societa Editrice Universo, 2014)
Aims To evaluate the functional outcomes of a delayed (>6 months post-injury) and combined reconstruction of grade III posterior cruciate ligament (PCL) and grade III posterolateral corner (PLC) deficiencies.